Apexification in an adult patient's tooth: a 9-year case report - Ms Yura Lee; Dr Miyeon Kim (Elsevier, 2023)
Introduction: Immature permanent teeth with open apex can be challenging in endodontic treatment along with its restoration. Apexification is widely applied in teenager patients but rarely used in the adult population. This case report aims to share a successful apexification application in the mandibular premolar with an open apex and periapical lesion of an adult patient. Case Description: A 31-year-old male visited Dental Hospital Department of Conservative with chief complaint of regular checkup. Intraoral examination revealed an abraded dens evaginatus in the center of the occlusal surface of tooth #35. The tooth showed a negative response to the cold test, hot test and percussion. An immature root with a blunderbuss apex and a periapical shadow were demonstrated by X-ray radiography. Thus, the clinical diagnosis of tooth #35 was pulp necrosis with chronic periapical periodontitis. For the treatment of this tooth, apexification procedure was performed by using Proroot MTA (Dentsply, Tulsa, OK). The treatment was considered successful with no clinical signs or symptoms, complete apex closure and decreased area of periapical shadow as seen on 9- year follow-up radiograph. Discussion: Our current case report demonstrated that MTA can lead to apex closure, supporting the hypothesis that apexification can also be applied to adults. Apexification with a novel biocompatible material like MTA is an effective management of adult patients' teeth with open apex. However, Systematic study with more samples is needed to further confirm the efficiency of apexification with MTA in adult patients. Conclusion/Clinical Significance: Our current case report indicates that patient's age may not be the critical limitation for apexification.